2010
DOI: 10.1148/rg.301095057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Logistic Regression and Artificial Neural Network Models in Breast Cancer Risk Estimation

Abstract: Computer models in medical diagnosis are being developed to help physicians differentiate between healthy patients and patients with disease. These models can aid in successful decision making by allowing calculation of disease likelihood on the basis of known patient characteristics and clinical test results. Two of the most frequently used computer models in clinical risk estimation are logistic regression and an artificial neural network. A study was conducted to review and compare these two models, elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 23 publications
2
105
0
1
Order By: Relevance
“…LR and the ANN are the most frequently used computer models in clinical risk estimation [19]. The advantage in use of the ANN is the capacity to model complex non-linear relationships between independent and predictor variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LR and the ANN are the most frequently used computer models in clinical risk estimation [19]. The advantage in use of the ANN is the capacity to model complex non-linear relationships between independent and predictor variables.…”
Section: Discussionmentioning
confidence: 99%
“…If Y is denoted as an indicator of cancer, the probability of cancer, given x i , is as follows [19,26]:…”
Section: Lr Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Though data learning and training in the hidden layer is not transparent to the user, ANN is simple to implement as it requires minimal statistical training. The logistic regression method utilises a simpler linear model, and unlike ANN which can handle arbitrary relationships between input and output variables, it can only be used if such relationships can be explicitly identified (Ayer et al, 2010). Thus, the logistic regression method is not as robust as ANN.…”
Section: Machine Learningmentioning
confidence: 99%
“…For this purpose, a large number of breast cancer risk factors have been identified and investigated in the breast cancer screening field. In the cancer epidemiology field, a number of breast cancer risk assessment models have been identified, which rely primarily on the combination of several well-known risk factors, such as age, family history, information on special genotypes and breast density [4][5][6]. With the exception of age and carrying specific gene mutations that only apply to a very small fraction of the population, many studies have shown that the breast density is the strongest breast cancer risk indicator [7,8].…”
Section: Introductionmentioning
confidence: 99%